2012
DOI: 10.4236/psych.2012.37077
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Orientations of Turkish Counselor Trainees: The Role of Thinking Styles, Epistemology and Curiosity

Abstract: Counselors vary in personality traits, worldviews, epistemic values, cognitive styles, and developmental influences, and these variations in return effect their choice of a guiding theory. This study addresses the variables associated with the theoretical orientations of Turkish psychological counseling students. Participants completed measures of curiosity, thinking styles, epistemological beliefs and a questionnaire on their theoretical choices. Three separate discriminant analysis were conducted to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…In a study of U.S. psychologists-in-training, Boswell and colleagues (2009) found that the majority of students held assumptions that supported eclectic and integrated orientations of counseling and psychotherapy, followed by the most common single theories of psychodynamics and humanism. Demir and Gazioglu (2012) also found that the majority of their Turkish counseling student participants preferred eclectic and integrative orientations, with cognitive and humanistic approaches next.…”
Section: Theoretical Endorsements Among Counseling Studentsmentioning
confidence: 88%
See 1 more Smart Citation
“…In a study of U.S. psychologists-in-training, Boswell and colleagues (2009) found that the majority of students held assumptions that supported eclectic and integrated orientations of counseling and psychotherapy, followed by the most common single theories of psychodynamics and humanism. Demir and Gazioglu (2012) also found that the majority of their Turkish counseling student participants preferred eclectic and integrative orientations, with cognitive and humanistic approaches next.…”
Section: Theoretical Endorsements Among Counseling Studentsmentioning
confidence: 88%
“…There is limited research of U.S. counselor education programs regarding the theoretical orientations of master's level students. Most of the empirical research regarding the specific theories endorsed by students has focused on psychologists-in-training (Boswell, Castonguay, & Pincus, 2009) or counseling trainees in international undergraduate counseling programs (Demir & Gazioglu, 2012;Sumari, Mohamad, & Ping, 2009). Nevertheless, information gleaned from research can inform the current study by shedding light on theoretical assumptions of novice mental health practitioners.…”
Section: Theoretical Endorsements Among Counseling Studentsmentioning
confidence: 99%
“…A study of Turkish counsellor trainees (Demir & Gazioglu, 2012) found that eclectic approaches were favoured most, followed by cognitive and humanistic approaches. In Sibbald's UK research, counsellors were listed as including community psychiatric nurses, "practice counsellor", clinical psychologists, psychiatrist, health visitor and practice nurses.…”
Section: European Area Studies-emphasizing the Ukmentioning
confidence: 99%
“…CBT has been identified as the most commonly endorsed psychotherapeutic approach in many countries across the world: it is the leading therapeutic approach or one of the leading approaches cited in the US (e.g., Cook et al, 2010), UK (e.g., Hollanders & McLeod, 1999), Denmark (e.g., Jacobsen et al, 2012), Turkey (Demir & Gazioglu, 2012), and Malaysia (Mohamad & Rahman, 2011)-but not in Argentina where again the psychodynamic approach predominated (Muller, 2008). Jacobsen et al (2012) though indicating CBT was highly ranked (as indicated above), also indicated that the Danish psychologists equally or nearly equally emphasised analytic/psychoanalytic orientations.…”
Section: Theoretical Orientationsmentioning
confidence: 99%
“…In the last decades, psychotherapy researchers have been interested in issues associated with personal epistemology in different domains related to clinical practice, such as practitioner education and theoretical orientation choice (Arthur, 2000(Arthur, , 2001Demir & Gazioglu, 2012;Heffler & Sandell, 2009;Schacht & Black, 1985); therapist self-care (Brucato & Neimeyer, 2009); working alliance and use of therapeutic techniques (Lee, Neimeyer, & Rice, 2013); and therapy outcomes (Toska, Neimeyer, Taylor, Kavas, & Rice, 2010). This growing interest has rested on the premise that psychotherapists' epistemic commitments may influence affective, behavioral, and cognitive aspects related to their practice.…”
mentioning
confidence: 99%